Z kalicha ibiškového kvetu: Vietnamské rozprávky - Moric, Rudo: 1921-1985; Baricová-Dočevská, Gusta; Čačko, Peter: 1936-; Čakovská, Marta; Dašková, Kveta: 1935-; Ferková, Hana: 1927-2005; Haľamová, Maša: 1908-1995; Turan, Ján: 1932-; Kellenberger, Ľubomír: 1921-1971 (Mladé letá, 1972)
Kniha ponúka krásne vietnamské rozprávky.